Proceedings of the International Conference on Technology and Vocational Teachers (ICTVT 2017) 2017
DOI: 10.2991/ictvt-17.2017.54
|View full text |Cite
|
Sign up to set email alerts
|

Adobe Flash CS6-Based Interactive Multimedia Development for Clothing Pattern Making

Abstract: Abstract--In the Curriculum 2013, the Pattern Making subject is oriented towards the basic knowledge of students in making clothing patterns. Competencies that must be achieved by students in the pattern-making subject include changing blouse, shirt, and skirt patterns. Once students is competent in making the pattern, then they can continue learning master the next competency. Pattern Making Course is an early stage of the process of clothes making. Pattern making includes processes such measuring, drawing pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Based on the explanation above, it can be concluded that the three-dimensional module with Optitex is suitable for the learning process of fashion student pattern construction. This finding is in line with research conducted by Ampera (2017) and Taya, Shibuya, and Nakajima (1995), where the study developed a blazer patternmaking learning media based on Adobe Flash CS6 for students of class Fashion. The research stated that learning media based on Adobe Flash CS6 could be used as a learning medium.…”
Section: Results Of Large Group/field Trialsupporting
confidence: 90%
“…Based on the explanation above, it can be concluded that the three-dimensional module with Optitex is suitable for the learning process of fashion student pattern construction. This finding is in line with research conducted by Ampera (2017) and Taya, Shibuya, and Nakajima (1995), where the study developed a blazer patternmaking learning media based on Adobe Flash CS6 for students of class Fashion. The research stated that learning media based on Adobe Flash CS6 could be used as a learning medium.…”
Section: Results Of Large Group/field Trialsupporting
confidence: 90%
“…The technology used is the Adobe Flash CS6 application. Adobe Flash is an application that is widely used by designers to produce work in the field of animation (Ampera, 2017). With this media, teachers can develop learning media and other interactive materials (Wati & Nugraha, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Macromedia Flash has been produced in several versions. The latest version of Macromedia Flash is Macromedia Flash 8 [21]. And now Flash has switched vendors to Adobe.…”
Section: Figure 2 Classification Of Uml Diagram Typesmentioning
confidence: 99%